2000
DOI: 10.1191/096120300680198944
|View full text |Cite
|
Sign up to set email alerts
|

Acute optic neuropathy and transverse myelopathy in patients with antiphospholipid antibody syndrome: Favorable outcome after treatment with anticoagulants and glucocorticoids

Abstract: We describe two patients with established antiphospholipid syndrome, who during periods of subtherapeutic anticoagulation, developed acute optic neuropathy and transverse myelopathy. Treatment with optimal anticoagulation and high dose glucocorticoids was followed by resolution of the neurologic deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
1
14
0
1
Order By: Relevance
“…Although corticosteroids are not generally recommended in the treatment of APS, their use may be justified in patients with desperate situations, such as catastrophic APS with undefined therapeutic mechanism(s) (52,53). In the present study, DEX was shown to exhibit a dose-dependent inhibitory effect on both the basal and aCL-induced MCP-1 production (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…Although corticosteroids are not generally recommended in the treatment of APS, their use may be justified in patients with desperate situations, such as catastrophic APS with undefined therapeutic mechanism(s) (52,53). In the present study, DEX was shown to exhibit a dose-dependent inhibitory effect on both the basal and aCL-induced MCP-1 production (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, organic involvement in patients with antiphospholipid syndrome can appear on a spectrum from rapidly progressive to clinically silent and indolent. Furthermore, findings may either be isolated and limited to an end organ or widely disseminated and associated with systemic manifestations of antiphospholipid syndrome 14 …”
Section: Discussionmentioning
confidence: 99%
“…Of these medications, only warfarin has been shown to definitively be effective 11 . It is believed that glucocorticoid therapy, in addition to the anti‐inflammatory effects, may also protect neural tissues from ischemic injury, stabilize the vascular endothelium, and restore the blood‐brain barrier to normal 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several patients have been observed who had recurrent episodes, with recurring hyperintensities and eventually cord atrophy [56]. Most patients responded to steroid pulse therapy with or without anticoagulation and some showed further response to cyclophosphamide [57]. Four of our patients have been treated with steroids in the acute phase and then by pulses of cyclophosphamide with continued improvement over 1 year.…”
Section: Myelopathymentioning
confidence: 83%